Development of Jernang Non-timber Forest Product in the Bukit Dua Belas National Park Area Jambi can be Jernang (Daemonorops draco (Willd.) Blume ) Sunscreen With SPF 15 - Uce Lestari; Revis Asra; Yusnelti (CV. Media Digital Publikasi Indonesia, 2023)
The Suku Anak Dalam (SAD) in the Bukit Dua Belas National Park region of Jambi produce jernang, one of the non-timber forest products, and it has promise as a sunscreen because it contains polyphenolic chemicals that may absorb UV radiation. The purpose of this study is to ascertain the Sun Protection Factor (SPF) of jernang sunscreen and its physical characteristics. The 1% (FI), 2% (FII), and 3% (FIII) jernang resin concentrations were used to create jernang sunscreen. Organoleptic, pH, homogeneity, viscosity, stickiness, spreadability, kind of cream, and stability are examples of physical qualities. The results indicated that, while all sunscreen formulae have SPF values ranging from 11.87 to 12.69, in the extra-protection category, the SPF value reached decreased with increasing jernang resin content